Two compound heterozygous variants in the CLN8 gene are responsible for neuronal cereidolipofuscinoses disorder in a child: a case report - Baltar, Federico; Simoes, Camila; Garagorry, Francisco; Graña, Martín; Rodríguez, Soledad; Haydée Aunchayna, María; Tapié, Alejandra; Cerisola, Alfredo; González, Gabriel; Naya, Hugo; Spangenberg, Lucía; Raggio, Víctor (Frontiers in Pediatrics, 2024)
Background: Neuronal Ceroid Lipofuscinosis (NCL) disorders, recognized as the primary cause of childhood dementia globally, constitute a spectrum of genetic abnormalities. CLN8, a subtype within NCL, is characterized by cognitive decline, motor impairment, and visual deterioration. This study focuses on an atypical case with congenital onset and a remarkably slow disease progression. Methods: Whole-genome sequencing at 30x coverage was employed as part of a national genomics program to investigate the genetic underpinnings of rare diseases. This genomic approach aimed to challenge established classifications (vLINCL and EPMR) and explore the presence of a continuous phenotypic spectrum associated with CLN8. Results: The whole-genome sequencing revealed two novel likely pathogenic mutations in the CLN8 gene on chromosome 8p23.3. These mutations were not previously associated with CLN8-related NCL. Contrary to established classifications (vLINCL and EPMR), our findings suggest a continuous phenotypic spectrum associated with CLN8. Pathological subcellular markers further validated the genomic insights. Discussion: The identification of two previously undescribed likely pathogenic CLN8 gene mutations challenges traditional classifications and highlights a more nuanced phenotypic spectrum associated with CLN8. Our findings underscore the significance of genetic modifiers and interactions with unrelated genes in shaping variable phenotypic outcomes. The inclusion of pathological subcellular markers further strengthens the validity of our genomic insights. This research enhances our understanding of CLN8 disorders, emphasizing the need for comprehensive genomic analyses to elucidate the complexity of phenotypic presentations and guide tailored therapeutic strategies. The identification of new likely pathogenic mutations underscores the dynamic nature of CLN8-related NCL and the importance of individualized approaches to patient management.